2021
DOI: 10.1177/08404704211046604
|View full text |Cite
|
Sign up to set email alerts
|

Community-informed, integrated, and coordinated care through a community-level model: A narrative synthesis on community hubs

Abstract: We identify the core services included in a community hub model of care to improve the understanding of this model for health system leaders, decision-makers in community-based organizations, and primary healthcare clinicians. We searched Medline, PubMed, CINAHL, Scopus, Web of Science, and Google from 2000 to 2020 to synthesize original research on community hubs. Eighteen sources were assessed for quality and narratively synthesized (n = 18). Our analysis found 4 streams related to the service delivery in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, this does not need to be the case for prehabilitation and rehabilitation. Indeed, patient engagement and adherence can be improved by providing services that are more geographically accessible, i.e., nearer to patients and with good travel connections [34]. To ensure equal care across the whole population of the South Yorkshire region, the intention is to expand Active Together such that every patient with a cancer diagnosis can access equitable, high-quality prehabilitation and rehabilitation services, without barriers based on geography.…”
Section: Scalability and Expansionmentioning
confidence: 99%
“…However, this does not need to be the case for prehabilitation and rehabilitation. Indeed, patient engagement and adherence can be improved by providing services that are more geographically accessible, i.e., nearer to patients and with good travel connections [34]. To ensure equal care across the whole population of the South Yorkshire region, the intention is to expand Active Together such that every patient with a cancer diagnosis can access equitable, high-quality prehabilitation and rehabilitation services, without barriers based on geography.…”
Section: Scalability and Expansionmentioning
confidence: 99%
“…Older adults are much more likely to continue with, and make social connections, in a physical activity program they enjoy (Creighton et al 2022). In a synthesis of research on community hubs performed between 2000 and 2020, it was found that community hubs offer a range of services throughout the community; however, of the 18 studies reviewed, six of these were aimed at social care for older adults with chronic illness or disability, and none of them included physical activity (Manis et al 2022). Another review suggested that physical activity was particularly good for vulnerable older people, as it improved their functional ability; however, it also noted that physical activity alone did not reduce loneliness (Shvedko et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One model of care coordination is the community hub model. This model focuses on community connection and community-informed service delivery, creating a network of providers that have a shared vision and goals related to medical care and integrating health and social care to ensure access to services and supports for individuals (Banarsee et al, 2018; Davidson et al, 2018; Evans et al, 2017; Manis et al, 2022). This model of care can enhance experience, satisfaction, and the efficiency of how care is delivered, particularly for those who have complex and intersecting needs (Shaw et al, 2017).…”
mentioning
confidence: 99%